Baduanjin exercise combined with moxibustion box for gastrointestinal dysfunction in the elderly: a protocol of prospective, randomized controlled trial - Zhu, Jing; Zhang, Dongxia; Yang, Lu; Liang, Hong; Liu, Qingyan; Liang, Jinyan; Li, Zunjiang; Ding, Banghan; Zheng, Danwen (Frontiers in Medicine, 2025)
ObjectiveTo synthesize and compare the results of a controlled trial of traditional Chinese medicine (TCM) nursing techniques, Baduanjin exercise (BDJE) combined with moxibustion box (MB) intervention measures, to improve gastrointestinal dysfunction (GID) in the elderly.DesignA prospective randomized controlled trial.MethodParticipants were recruited from the Guangdong Provincial Hospital of Traditional Chinese Medicine and randomly assigned to either the intervention group or the conventional treatment group using a random number table generated by SAS software. The intervention measures included the use of BDJE plus MB for 2 weeks. The main outcome measures were the Gastrointestinal Symptom Rating Scale (GSRS) and clinical efficacy. Secondary outcome measures included bowel sounds, changes in abdominal circumference, frequency of bowel movements per day, and stool morphology. Measure the outcome before and 2 weeks after treatment.DiscussionGastrointestinal dysfunction (GID) has a high incidence rate in severely ill patients and is associated with poor prognosis. Elderly patients with GID are affected by this disease, which reduces their quality of life and, subsequently, affects their mental health. The treatment of elderly patients with GID includes Western drug treatment (WDT) and traditional Chinese medicine. However, the therapeutic effect of WDT during enteral nutrition in critically ill patients is unsatisfactory. BDJE combined with MB in TCM nursing technology has the characteristics and advantages of simple operation, low price, convenience, and effectiveness, and is more easily accepted by patients. Therefore, this study aimed to compare the clinical efficacy of WDT and the combination of BDJE and MB in elderly patients with GID.ImpactThis study provides evidence of the clinical efficacy of BDJE combined with MB in treating elderly patients with GID.Trial registrationhttp://itmctr.ccebtcm.org.cn/, Identifier, ITMCTR2025000167.